Exploring the challenges and opportunities of gap year institutions in selected provinces in South Africa - Hattingh, Minke (North-West University (South Africa), 2022)
Very little research has been conducted on the value, opportunities, and challenges of gap year institutions within the South African realm. Not very much has been done to understand the various aspects of a gap year and the impact participation in a gap year has on South African students’ personal development and academic performance. This study’s first primary objective was to give an exploratory and descriptive view of the value of gap year institutions in South Africa and the impact on personal development and academic performance. The study furthermore sought to uncover the experiences and perceptions of the students regarding participating in a structured gap year. The second primary objective of this study was to conclude the gap year industry's challenges and determine the opportunities. The literature review of Chapter 2 provides insight into the gap year industry required for the study. Firstly, this study used phenomenological analysis on twelve students who participated in structured gap year before their tertiary studies. This was done to conclude the student’s perception of participating in a gap year and determine the value of a gap year. Secondly, data was also collected from seven managers of gap year institutions to accomplish the second primary objective, establishing the challenges and opportunities within the gap year industry. The value of a gap year was also discussed from their perspective. The empirical research was the second phase of the study. This study was conducted using a qualitative research method along with semi-structured interviews. Thematic analysis was used as the data analysis technique. The quantitative interview procedure identified four main themes from the data collected from students who participated in a gap year and four main themes from the managers of gap year institutions. The participants in this study also described several sub-themes and categories. The study concluded recommendations of how gap year institutions can overcome challenges and exploit opportunities. The consequent advice was that taking a gap year is beneficial and holds great value to the students who participated in one. Suggestions for further studies were also made in this regard.
MBA, North-West University, Potchefstroom Campus
Keywords: GAP year; Structured gap year program; Gap year institution; Personal development; Drop out; Course changing; Higher education; Tertiary studies; Academic performance; Matriculates; Challenges; Opportunities; Values